Hubungan Pengetahuan Perawat Dengan Pelaksanaan Keselamatan Pasien (Patient Safety) Di Ruang Rawat Inap Rsud Kardinah Tegal - Luthfi Fauzi Baihaqi; Etlidawati Etlidawati (Jurnal Keperawatan Muhammadiyah, 2020)
Background: Unwanted events such as patients falls are still common and can not be avoided even though the management of patients falls has been implemented,due to lack of nurses knowledge about patient safety. Misinterpretation when reading prescriptions given by doctors is an incident that still occurs and can be dangerous to patients in addition to incidents of patients falls that can be found. Therefore, it is necessary to link the knowledge of nurses with the implementation of patient safety. Objective: To find out the relation between nurses knowledge and the implementation of patient safety in the inpatient ward of Kardinah Tegal Hospital. Method: This study uses a method taken with a cross-sectional approach. The sample of this study was nurses in class III inpatients at Kardinah Tegal Hospital as many as 80 respondents taken by total sampling technique. Data analysis uses chi-square test. Results: The level of knowledge is good (51.2%), enough (23.8%), and bad (25%). The implementation of patient safety was good (86.3%) and enough (13.8%). Chi-square Test results obtained p-value = 0,000 (p <0.05) showed a relationship between the knowledge of nurses with the implementation of patient safety. Conclusion: There is a relationship between nurses knowledge and the implementation of patient safety in class III inpatients at Kardinah Tegal Hospital. Keywords: Knowledge, Implementation of Patient Safety, Nurses